IMPLEMENTASI PERATURAN DAERAH NOMOR 9 TAHUN 2011 TENTANG GERAKAN CINTA KELUARGA MISKIN (GENTAKIN) DI KECAMATAN TENAYAN RAYA KOTA PEKANBARU - Syaprianto, Syaprianto (UIR PRESS, 2018)
Poverty is seen as the root cause of social problems that must be overcome by the Government then to cope with poverty, the City Government of Pekanbaru issued Local Regulation No. 9 of 2011 About Gerakan Cinta Keluarga Miskin (Gentakin) in Tenayan Raya district of Pekanbaru city. This study aims to determine the Implementation of Regional Regulations and obstacles by using the theory of Edward III and qualitative research methods with the aim of describing, analyzing and trying to describe the Implementation of Regional Regulation by interviewing directly and deeply to informants who are considered most know by using purposive sampling technique. The results of this study indicate that the socialization conducted by the Government of Pekanbaru City has been implemented but the socialization is considered not maximal so there are still people and donors who do not know the form of guidance done in addition to the shortage of employees, operational funds also become obstacles so that supervision of beneficiaries business has not been maximally consequently the people who receive the aid there are not using the help as it should so then the city government of Pekanbaru is expected to provide real guidance and to monitor directly the development of assistance that has been given and hope the city government of Pekanbaru can give awards for beneficiaries who succeed in his business and sanction people who do not use the aid.